2017
DOI: 10.18632/oncotarget.23186
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of regenerating liver-3 is expressed in acute lymphoblastic leukemia and mediates leukemic cell adhesion, migration and drug resistance

Abstract: Phosphatase of regenerating liver-3 (PRL-3/PTP4A3) is upregulated in multiple cancers, including BCR-ABL1- and ETV6-RUNX-positive acute lymphoblastic leukemia (ALL). With this study, we aim to characterize the biological role of PRL-3 in B cell ALL (B-ALL). Here, we demonstrate that PRL-3 expression at mRNA and protein level was higher in B-ALL cells than in normal cells, as measured by qRT-PCR or flow cytometry. Further, we demonstrate that inhibition of PRL-3 using shRNA or a small molecular inhibitor reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…We found PRL-3 was highly expressed in T-ALL patient samples and cell lines, consistent with studies reporting PRL-3 upregulation in solid tumors 42 and B-ALL 43 . Importantly, we used two different animal models to demonstrate an oncogenic role for PRL-3 in T-ALL, which, to the best of our knowledge, is the first in vivo study demonstrating this finding.…”
Section: Discussionsupporting
confidence: 91%
“…We found PRL-3 was highly expressed in T-ALL patient samples and cell lines, consistent with studies reporting PRL-3 upregulation in solid tumors 42 and B-ALL 43 . Importantly, we used two different animal models to demonstrate an oncogenic role for PRL-3 in T-ALL, which, to the best of our knowledge, is the first in vivo study demonstrating this finding.…”
Section: Discussionsupporting
confidence: 91%
“…We found that PTP4A3 was highly-expressed in T-ALL patient samples and cell lines compared with healthy PBMCs, which is consistent with studies reporting PTP4A3 upregulation in solid tumors [58] and B-ALL [41]. More importantly, we used two different and unique animal models to demonstrate a oncogenic role for PTP4A3 in T-ALL: overexpression of PTP4A3 in the transgenic zebrafish T-ALL model showed that PTP4A3 expression enhanced spreading of T-ALL cells out of the thymus and promoted their rapid entry into circulation, while human T-ALL cells with silenced PTP4A3 lost their ability to engraft and grow in NSG mice.…”
Section: The Identification and Characterization Of Important Driverssupporting
confidence: 91%
“…PTP4A3 has been reported as a downstream target of FMSlike tyrosine kinase 3 internal tandem duplication (FLT3-ITD), which is a prevalent mutation in AML, where it leads to activation of activator protein 1 (AP-1) transcription factor and contributes to AML progression in vitro and in vivo via an unknown mechanism [17,40]. Recently, it was demonstrated that PTP4A3 is highly expressed in B-cell Acute Lymphoblastic Leukemia (B-ALL) patient samples, and in vitro studies showed it played a role in modulating cell migration and resistance to the chemotherapy cytarabine [41]. Here we provide both in vitro and in vivo evidence for a novel role for PTP4A3 in T-ALL.…”
Section: Introductionmentioning
confidence: 99%
“…PRL-3 is highly expressed in many cancer types and is a proven oncoprotein. It has well-established roles in tumor cell invasion and metastasis, and data suggests it may also be involved in cancer cell proliferation and drug resistance 47,48 . There have been increasing efforts to identify PRL-3 inhibitors.…”
Section: Discussionmentioning
confidence: 99%